ADHERENCE TO SWALLOWING REHABILITATION EXERCISES IN HEAD AND NECK CANCER PATIENTS WITH RADIOTHERAPY: CURRENT SITUATION AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objectives: (1) To describe the compliance with swallowing rehabilitation exercises among head and neck cancer patients undergoing radiotherapy at Nghe An Oncology Hospital, and (2) To analyze factors associated with adherence levels in this population. Methods: An analytical cross-sectional study was conducted on 103 head and neck cancer patients indicated for definitive or adjuvant radiotherapy from January 2025 to September 2025. Adherence to seven swallowing rehabilitation exercises was evaluated via face-to-face interviews on the final day of the radiotherapy course. Data were processed using SPSS 26.0, and logistic regression analysis was performed to identify associated factors (p
Keywords: Head and neck cancer, Swallowing rehabilitation, Radiotherapy, Treatment compliance.